The equation is x^2 - x - 12 = 0
First you factor the equation.
(x - 4)(x + 3) = 0
You can FOIL this to check your answer so far
(x)(x) + (3)(x) - (4)(x) - (12) = 0
x^2 - x - 12 = 0
That's right so far. So now you need to look at the equation you have.
(x - 4)(x + 3) = 0
This is telling you that to get zero, either the (x - 4) term must be zero or the (x + 3) term must be zero (because anything multiplied by zero equals zero).
x - 4 = 0 and x + 3 = 0
x = 4 and x = -3
You can also see this graphically by plotting a graph of x^2 - x - 12 and seeing where the graph will intersect the x-axis. You will also see there that it does it at x = 4 and x = -3.
2007-04-04 06:35:24
·
answer #1
·
answered by RyanGoff 2
·
0⤊
0⤋
Original Equation:
x^2 - x -12 =0
Step 1 Break it down into factors (see below for better explantion on how to do this)
(x-4)(x+3) =0
Step 2 Solve by setting each factor to zero. (See below on why)
x-4 = 0 or x+3 = 0
Step 3 solve each equation for x
(Equation of factor 1) add 4 to each side to get x=4
(Equation of factor 2) subtract 3 from each side to get x = -3
Answer x = 4 or x = -3
The form of this equation is a quuadratic form.
ax^2 + bx + c = 0
in my mind I determine what a, b, and c were
a being the coefficient of x^2 is 1
b being the coefficient of x is -1
c being the constant is -12
Since the coefficient of the square (a) is 1 we need no modification to the origianal equation.
Take the numbers that when multiplied equal -12 (c the constant) which are:
-12 * 1
-6 * 2
-4 * 3
-3 * 4
-2 * 6
-1 * 12
Now add the factors until you find coeffecient of the x (b) to the first (which in this case is -1) .
-12 + 1 = -11
-6 + 2 = -4
-4 + 3 = -1
bingo we put it in factor form.
(x - 4)(x + 3)
just as a precaution you can re-multiply this out to check to see if you can gett back to your original equuation
(x-4)
*(x+3)
--------------
3x -12
x^2 -4x + 0
---------------------
x^2 -x -12
Now we take our factor form (x-4)(x+3) = 0 and set each factor to zero because if a * b = 0 then either a or b has to be zero. (Note not sure what theorem that is from because my grade school was so long ago also not sure of all my terminology hope its right)
Hope that helps and I hope I just didn't do your homework for you and you really needed help.
2007-04-04 06:49:50
·
answer #2
·
answered by LTD4 2
·
0⤊
0⤋
question type a million : For this equation x^2 - x - 12 = 0 , answer right here questions : A. locate the roots using Quadratic formulation ! answer type a million : The equation x^2 - x - 12 = 0 is already in a*x^2+b*x+c=0 sort. through matching the consistent place, we can derive that the fee of a = a million, b = -a million, c = -12. 1A. locate the roots using Quadratic formulation ! remember the formulation, x1 = (-b+sqrt(b^2-4*a*c))/(2*a) and x2 = (-b-sqrt(b^2-4*a*c))/(2*a) We had understand that a = a million, b = -a million and c = -12, we in simple terms could desire to subtitute the fee of a,b and c interior the abc formulation. So x1 = (-(-a million) + sqrt( (-a million)^2 - 4 * (a million)*(-12)))/(2*a million) and x2 = (-(-a million) - sqrt( (-a million)^2 - 4 * (a million)*(-12)))/(2*a million) that is grew to become into x1 = ( a million + sqrt( a million+40 8))/(2) and x2 = ( a million - sqrt( a million+40 8))/(2) Which make x1 = ( a million + sqrt( 40 9))/(2) and x2 = ( a million - sqrt( 40 9))/(2) We have been given x1 = ( a million + 7 )/(2) and x2 = ( a million - 7 )/(2) So we've the solutions x1 = 4 and x2 = -3
2016-12-08 18:10:02
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
X^2 -x -12 = 0
(x-4) (x+3) = 0 (factoring)
x = 4,-3
2007-04-04 06:19:48
·
answer #4
·
answered by rwhitehead837 2
·
0⤊
0⤋
X^2 - X - 12 = 0
(X - 4)(X +3) = 0
(X - 4) = 0 and/or (x + 3) = 0
so...
x = 4, -3
2007-04-04 06:22:44
·
answer #5
·
answered by Jenniffer 2
·
0⤊
0⤋
You could use the quadratic formula to solve but factoring, you get (x+3)(x-4). When you set each of these to zero, the answers are: x= -3 and x = 4.
2007-04-04 06:24:32
·
answer #6
·
answered by kathyw 7
·
0⤊
0⤋
x^2-x-12=0
Factor as follows:
(x-4)(x+3) = 0
Now set each factor = 0
x-4 = 0 --> x=4
(x+3) =0 --> x = -3
2007-04-04 06:25:33
·
answer #7
·
answered by ironduke8159 7
·
0⤊
0⤋
X * 2 -x-12=0
X*2-x=12+0(12)
X*2-x=12
X2-x=1x
(1)x=12
divide both sides by one
x=12
Check it
X*2(x squared)-x-12=0
subsitute
12*2-12-12=0
24-12-12=0
22-12=12 (x)
x=12
2007-04-04 06:27:33
·
answer #8
·
answered by nibor194 3
·
0⤊
0⤋
x= {4, -3}
This factors into (x+3) ( x-4) = 0
So, x= {4, -3}
2007-04-04 06:19:28
·
answer #9
·
answered by kash 3
·
0⤊
0⤋
4!!!
4 squared is 16...then subtract 4 which equals twelve...then subtract 12 to get zero
2007-04-04 06:17:26
·
answer #10
·
answered by Star86 2
·
0⤊
1⤋